Kajian Implementasi Permendes Nomor 19 Tahun 2017 Dalam Penetapan Prioritas Penggunaan Dana Desa di Kabupaten Barito Kuala - Qubayla, Farah; Jamaluddin, Jamaluddin (Jurnal Publisitas, 2021)
Permendes (Regulation of the Minister of Villages, Development of Disadvantaged Areas, and Transmigration) Number 19 of 2017 regulates priorities for the use of village funds in 2018.The determination of priority for the use of village funds aims to serve as a guideline and reference for the implementation of authority, a reference for Regency / City Government in preparing technical guidelines for the use of village funds and a reference for the Central Government in monitoring. and evaluation of the implementation of the use of village funds. This study used qualitative methods and was conducted to study the implementation problems of Permendes No. 19 of 2017 and recommendations in the form of concrete steps that need to be taken by the government in Barito Kuala Regency. The findings and recommendations in this study resulted from a normative review of policies related to the Permendes No. 19 of 2017 as well as empirical studies on the use of village funds in eight selected villages in various sub-districts in Barito Kuala Regency. Through this research it is known that communication, resources, disposition and bureaucratic structure greatly determine how the implementation of the Permendes in determining village fund priorities. Village funds received in all villages in Barito Kuala Regency are generally prioritized for infrastructure development, which absorbs about 70% of the total funds. Through this research, it is hoped that there will be a design model for determining the priority of the use of village funds which is possible to reduce the rural poverty rate in Barito Kuala Regency.